Facebook as a Knowlegde Sharing Platform at University of Nottingham Malaysian Campus - Chan Sui Ko, David Thomas (2009)
In an era where the future is determined by the ability to wisely use knowledge, universities have a crucial role to play being in the knowledge industry. While the essential role of universities toward the society is the dissemination of knowledge to the future manager and employees, their traditional classroom teaching is losing its popularity in the 21st century with the recognition that learning is collaborative. The emergence of social network site founded on the Web 2.0 technologies was found to have the necessary characteristics to promote knowledge management practice. The study examines the applicability of Facebook as a knowledge sharing platform at the University of Nottingham Malaysia Campus. The principles of knowledge management associated with Facebook are identified and the observations made from previous studies in the applicability of social network sites in education are investigated. The research examines the perceptions and expectations of the students in the adoption of Facebook as part of their curriculum.